2024
DOI: 10.1021/acs.jafc.3c08771
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linolenic Acid (CLnA) vs Conjugated Linoleic Acid (CLA): A Comprehensive Review of Potential Advantages in Molecular Characteristics, Health Benefits, and Production Techniques

Meijun Du,
Mengyue Gong,
Gangcheng Wu
et al.

Abstract: Conjugated linoleic acid (CLA) has been extensively characterized due to its many biological activities and health benefits, but conjugated linolenic acid (CLnA) is still not well understood. However, CLnA has shown to be more effective than CLA as a potential functional food ingredient. Current research has not thoroughly investigated the differences and advantages between CLnA and CLA. This article compares CLnA and CLA based on molecular characteristics, including structural, chemical, and metabolic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 194 publications
0
1
0
Order By: Relevance
“…In recent years, CLA as a functional fatty acid has been reviewed by researchers and scholars worldwide. Numerous studies have shown that it has a variety of physiological functions such as preventing atherosclerosis, regulating body immunity, reducing fat deposition, and promoting bone formation [ 3 , 4 , 5 , 6 ]. Natural CLA is mainly derived from ruminant meat products, dairy products, vegetable oil products, and some seafood [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, CLA as a functional fatty acid has been reviewed by researchers and scholars worldwide. Numerous studies have shown that it has a variety of physiological functions such as preventing atherosclerosis, regulating body immunity, reducing fat deposition, and promoting bone formation [ 3 , 4 , 5 , 6 ]. Natural CLA is mainly derived from ruminant meat products, dairy products, vegetable oil products, and some seafood [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%